Crashworthiness characteristics of natural ramie/bio-epoxy composite tubes for energy absorption application - Ghoushji, M.J. (Springer London, 2018)
Using metallic materials in automotive structures increases weight, fuel consumption and cost, therefore, certain trends have begun to use lightweight and cheaper materials. Fibre composites are used in automotive applications because they are stiff, lightweight and stronger than bulk material, as well as they have a comparable energy-absorbing capacity to that of metallic materials. The aim of this study is to investigate the potentials in natural ramie/bio-epoxy composite in crash energy absorption applications. Cubic specimens consisted of 12, 24 and 30 plies of ramie/bio-epoxy laminates with 50, 80 and 120Â mm long which were prepared by hand layup method. Static axial compression load was then applied and the energy-absorbing capability of the ramie/epoxy composite was evaluated. The crashworthiness characteristics of the composite tubes were evaluated by measuring the average and peak crushing load, specific energy absorption, total absorbed energy and crush force efficiency in quasi-static axial compression. The failure mode and behaviour of the tubes were investigated by taking photographs and recording the loadâdisplacement curves during the test accomplishment. The test results indicated that natural ramie/bio-epoxy composite tube has the great potential to be used as an effective energy-absorbing device. Â© 2018, Iran Polymer and Petrochemical Institute.